Frequency and risk of infection of bovine leptospirosis in two dairy farms of the coast and highlands of Peru - Llanco A., Luis (2017)
The study aimed to determine the seroprevalence and risk of infection of bovine leptospirosis in dairy farms of the Peruvian coast and highlands. A total of 88 blood samples were obtained in a farm in the area of Lima (coast) and 163 samples in a farm in the area of Huancayo (highlands), both belonging to the National University of San Marcos. The samples were analyzed by the microagglutination test to detect antibodies to serovars canicola, pomona, icterohaemorrhagiae and hardjo. Seroprevalences of 14.8 and 12.3% were found in Lima and Huancayo farms respectively, where the serovar icterohaemorrhagiae was the only detected in Lima and serovars icterohaemorrhagiae and hardjo in Huancayo farms.